Agronomic response of coriander (Coriandrum sativum L) to the application of organic fertilizers in the Pangua canton, Ecuador (FAVE Sección Ciencias Agrarias, 2025)
Organic fertilizers are among the alternatives used in sustainable agriculture. This study aimed to evaluate the agronomic response of cilantro to the application of organic fertilizers in Pangua Canton, Ecuador. The research was conducted at the Angamarca la Vieja farm, located in the Pilancon community, Ramón Campaña parish, Pangua Canton, Cotopaxi Province. The study lasted 90 days, covering both the establishment of the trial and the experimental work. Evaluations were carried out at three time points: 30, 60, and 90 days after sowing. A completely randomized design (DCA) was used, with five treatments and four replications, for a total of 20 experimental units. The fertilizers used were humus and compost, applied at two different rates (2 kg.m-2 and 4 kg.m-2), along with a control treatment (no fertilizer). The evaluated variables included plant height, number of leaves per plant, leaf length at harvest, root length, root fresh weight, plant fresh weight, yield per plot, and yield per hectare. The results showed that the use of organic fertilizers, based on humus and compost, significantly improved the growth and yield of cilantro. Notably, the 4 kg.m-2 dose of humus produced the best results for most variables, greatly outperforming the control and showing highly significant differences among the treatments. These findings underscore the importance of organic fertilizers in sustainable agriculture, contributing to both soil health and crop productivity.
Keywords: Organic fertilizers, sustainable agriculture, compost, humus, soil health.